RAPID DETECTION AND QUANTIFICATION OF THE FOODBORNE PATHOGENES BY REAL-TIME PCR - Chi, Lê Thị; Bình, Nguyễn Quốc (Vietnam Journal of Biotechnology, 2011)
We developed and assessed Real-Time PCR method for the rapid detection and quantification of infected in foodstuff pathogens, which are major bacteria in the intestinal tracts of human. The protocol used a universal culture preenrichment medium and PCR program that used direct enrichment culture broth with 5 sets of specific primers for 5 species of foodbome pathogenes were Escherichia coli. Salmonella spp., Shigella spp., Listeria monocytogenes and Bacillus cereus. The primers 100% specific as determined target species and no interference reaction with non-target species was observed. This method was simple that unnecessary DNA extraction, purification and had highly sensitive, detection limits from 1 to 10 copies/reaction as pure bacteria and 1-10 CFU/25 g food. After enrichment in TSBYE medium in 24 hours, samples infected microbial were determined the amount of cells from lO’to lO’cells/ml (R^ = 0.998) and the same colony counting method (p = 0.90). The accuracy, sensitivity and specificity is high, these averange values are 97.99, 98.05, and 95,60%. All the time to finish diagnosis only spent 4 - 3 0 hours in comparison with 5 - 7 days when using conventional culture method.